Goat Keeping and Goat Milk Products in Human Nutrition - Review - Csapóné Riskó, Tünde; Csapó, Zsolt (Applied Studies in Agribusiness and Commerce, 2019)
The aim of this paper is to review the status quo and future perspective of goat keeping and goat milk products, particularly emphasising the role of goat milk products in human nutrition. Across the globe, goats can be kept almost anywhere, even in poor surroundings. Considering the deteriorating geographical conditions due e.g. to global warming, the importance of goat and goat products will probably further increase. Goats can play an important role in the nutrition of the continuously increasing human population. The wool, meat and milk of goats are all valuable products. Goats are able to provide high quality products under diverse climate conditions and in extreme environments. Globally, more people drink jmilk from goats than from any other animal. Due to the components and profile of goat milk, it can be processed and a wide range of high quality and healthy value added products can be produced from it. Goat milk plays a decisive role in feeding starving and malnourished people in developing countries. In developed countries, a significant segment of many populations suffers from gastro-intestinal disorders and cow milk allergy. Goat milk plays an important role in the treatment of certain health problems. Moreover, due to its favourable effects on human health, goat milk has found a niche for itself in the trend towards healthy nutrition in developed countries, where connoisseur consumers are ensuring goat milk products a growing market share. In these countries, goat milk products, e. g. cheeses are also recognised as gastronomic and festive products.JEL Classification: Q13